Aspectos metodológicos en la enseñanza "on line" de lenguas extranjeras con un aula virtual - Marc Perdrix Forts; Juan de Dios Villanueva Roa (Universidad de Granada, 2010)
Lately foreign languages teaching have been developing new teaching allies in order to overcome shortcomings: they are the new technologies of information and communication or ICT. However, the challenges of ICT demand from teachers a real instruction both about the instrumental features of these technologies and in their educational possibilities. The different approaches and methodological options applied to the online teaching of foreign languages to develop the four basic skills, vocabulary access, activities and resources can be productively used in a virtual classroom in FL Teaching as we discuss in this paper..